MURAQABA AS A MINDFULNESS – BASED THERAPY IN ISLAMIC PSYCHOTHERAPY TO OVERCOME PORN ADDICTION - Adinda Tasya Kamila; Muhammad Novvaliant Filsuf Tasaufi (Psikoislamedia : Jurnal Psikologi, 2023)
Continuous exposure and consumption of pornography leads to pornography addiction. Islamic psychotherapy is able to be an alternative solution to this problem, one of which is muraqaba which is defined as individual awareness that Allah knows all that is in the heart, mind, and body. This paper uses a literature review method with an integrative review. The data used is the result of previous empirical studies, both quantitatively and qualitatively, in Indonesian and English. With applying muraqaba, individuals are able to be more aware of their feelings and thoughts, then more aware of the negative triggers of behavior so that it can be a step to avoid them. Can increase self-regulation leads individuals toward negative emotional states and self-reflection related to pornography. The awareness that comes from the application of muraqaba makes the individual to be careful in his actions, thoughts, feelings, and inner circumstances.